Ethnobotany study of banana plant sap (Musa sp.) as an incision remedy (Vulnus scissum) - Tri Cahyanto; Restu Anugrah; Nisrina Khairun Nisa; Triska Rosma; Yuna Islamiati (Biosfer: Jurnal Pendidikan Biologi, 2020)
The use of banana plant sap as an incision remedy has been carried out through generations in Citatah Village, Cipatat District, West Bandung Regency, Indonesia. This study aimed to examine the ethnobotanical utilization of banana plant sap as an incision remedy. The research was conducted using the snowball sampling technique by the method of structured observation and interviews with 30 respondents. The followings were tools and materials used for the research, a set of stationery, cameras, voice recorders, and laptops. The data obtained were analyzed using qualitative and quantitative descriptive analysis. The results showed that of the thirty respondents who knew the utilization of banana plant sap as wound remedy, only 60% were still using it. Parts of banana plants that were often used by the community was the banana plant shoots by 87% of the total respondents and banana leaf fronds by 13%. There was no specific type of banana used for this wound remedy. However, the type of banana most widely used by the community was ambon Banana (Musa paradisiaca var. sapientum) with a percentage of 20%, kulutuk/manggala banana (Musa balbisiana) 60%, and kepok Banana (Musa paradisiaca formatypica) 20%. Based on the results of the observation and interview, there were at least four benefits of using banana sap, namely preventing infection, sticking wounds, stopping bleeding, and drying the wound. While scientifically, this banana sap can be used as the wound remedy because it contains flavonoid compounds, saponins, triterpenoids, steroids, alkaloids, ascorbic acid, and tannins.